Penggunaan Media Pembelajaran Berbantuan PDF Corporate Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 5 Kota Ternate - Winda Umalekhoa; Zulkifli Ahmad; Hasna Ahmad (Universitas Khairun, 2023)
Teaching materials are one of the elements that support the teaching and learning process. Science learning is the most enjoyable learning so that in the process of learning biology on the material concept of the general characteristics of plants, especially in the sub-subject matter of ferns, it can be done with learning media assisted by corporate pdf. This study aims to (a) determine the validity of the use of PDF corporate learning media on the concept of material General characteristics of plants in class X students at SMA Negeri 5 Kota Ternate, (b) To find out the learning outcomes of SMA Negeri 5 Kota Ternate on the material characteristics concept -general characteristics of plants using coprate PDF media. Learning media validation was assessed by 4 validators to obtain media and material validation data, while learning outcomes data were analyzed using Excell 2010. The results of this study show that the media validation results obtained a score of 89% with valid criteria, while the material validation results obtained a score of 91.3%. with very valid criteria. The learning outcomes of class X IPA 4 at SMA Negeri 5 Kota Ternate experienced an increase in learning outcomes after the teaching and learning process used PDF Corporate assisted learning media.